Analisa Keseimbangan Pasar dan Reposisi Strategi Pemasaran Kayu Lapis - Dodik Ridho Nurrochmat; Tatang Tiryana (Institut Pertanian Bogor (IPB University), 2000)
The economic crisis’ turbulence blows down almost all of Indonesian export commodity, included plywood. Dissolution of JMB-Apkindo (Joint Marketing Body-Association of Indonesian wood based panel) as an implementation of Letter of Intent between Indonesian Government and International Monetary Fund caused reposition of the Indonesian plywood marketing. Impacts of the dissolution of JMB are weakening of the bargaining position of Indonesian plywood market and pushing down the international price of Indonesian plywood. The large scale of illegal logging that follows reformation’s euphoria is another problem which influences supply-demand of timber products. A right strategy in the forestry sector policy especially in plywood marketing is needed to overcome the above problems.